2005
DOI: 10.1086/432143
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Cardioventilatory Responses to Hypoxia in the Flathead Gray Mullet (Mugil cephalus) and Their Behavioral Modulation by Perceived Threat of Predation and Water Turbidity

Abstract: In hypoxia, gray mullet surface to ventilate well-oxygenated water in contact with air, an adaptive response known as aquatic surface respiration (ASR). Reflex control of ASR and its behavioral modulation by perceived threat of aerial predation and turbid water were studied on mullet in a partly sheltered aquarium with free surface access. Injections of sodium cyanide (NaCN) into either the bloodstream (internal) or ventilatory water stream (external) revealed that ASR, hypoxic bradycardia, and branchial hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 44 publications
0
89
0
Order By: Relevance
“…Catfish were fasted for 24 h prior to measurements in either condition, then individuals were transferred gently to respirometers without air exposure, to minimise effects of handling. There were four respirometer chambers immersed in well-aerated water in an outer bath (1 m 2 surface area, 21 cm water depth) with the entire setup screened behind tarpaulin so that routine air-breathing behaviour was not inhibited by fear of human presence (McKenzie et al, 1991(McKenzie et al, , 2007Shingles et al, 2005). Fish were placed in the respirometer in the evening between 18:00 h and 20:00 h and fish were then allowed 16 h to recover from handling.…”
Section: Bimodal Respirometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Catfish were fasted for 24 h prior to measurements in either condition, then individuals were transferred gently to respirometers without air exposure, to minimise effects of handling. There were four respirometer chambers immersed in well-aerated water in an outer bath (1 m 2 surface area, 21 cm water depth) with the entire setup screened behind tarpaulin so that routine air-breathing behaviour was not inhibited by fear of human presence (McKenzie et al, 1991(McKenzie et al, , 2007Shingles et al, 2005). Fish were placed in the respirometer in the evening between 18:00 h and 20:00 h and fish were then allowed 16 h to recover from handling.…”
Section: Bimodal Respirometrymentioning
confidence: 99%
“…Context has profound effects on air breathing in bimodal fishes. A reduced availability of resources -aquatic hypoxia -is a profound stimulant of air breathing (Chapman and McKenzie, 2009;Graham, 1997;Johansen, 1968;Lefevre et al, 2014a,b) but surfacing is inhibited if fishes perceive a risk of predation (Chapman and McKenzie, 2009;Shingles et al, 2005;Smith and Kramer, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…ASR places fish at significantly greater risk from aerial predation by birds . It has been demonstrated that if fish perceived a risk of predation they modulated the behavioral component of the ASR chemoreflex (Shingles et al, 2005). In Lake Victoria, Barbus neumayeri Fischer decreases the cost of ASR by having a more efficient oxygen-uptake method that reduces time at the surface and lower the threshold for ASR (Olowo & Chapman, 1996).…”
Section: Aquatic Surface Respirationmentioning
confidence: 99%
“…In Lake Victoria, Barbus neumayeri Fischer decreases the cost of ASR by having a more efficient oxygen-uptake method that reduces time at the surface and lower the threshold for ASR (Olowo & Chapman, 1996). Shingles et al (2005) found that exposure of flathead grey mullet to a model avian predator delayed the onset of ASR in hypoxia or in response to direct chemoreceptor stimulation with Sodium cyanide (NaCN). Additionally, the fish surfaced preferentially under a sheltered area in their experimental chamber or close to the walls.…”
Section: Aquatic Surface Respirationmentioning
confidence: 99%
See 1 more Smart Citation